Oral vitamin D3 5000 IU/day as an adjuvant in the treatment of atopic dermatitis: a randomized control trial - Sánchez‐Armendáriz, Karen; García‐Gil, Ana; Romero, Cesar A.; Contreras‐Ruiz, José; Karam‐Orante, Marcia; Balcazar‐Antonio, Denek; Domínguez‐Cherit, Judith (International journal of dermatology, 2018)
Background Vitamin D has immunomodulatory effects both in the innate and adaptive immune systems, and there is growing scientific evidence demonstrating its relevance in inflammatory processes such as AD. Hypothesis If vitamin D3 promotes the skin immune system, then it should improve the response to treatment of patients with AD. Methods A randomized, double‐blind placebo‐controlled clinical trial was conducted, which included 65 patients with AD according to Hanifin–Rajka criteria and the severity scale (SCORAD). The patients were divided into two groups to receive either vitamin D3 5000 IU/day (n = 33) or placebo (n = 32), plus baseline therapy (topical steroid, soap substitute, and emollient) during 3 months. Results Fifty‐eight of the 65 enrolled subjects were included in the analysis. At the end of the intervention, the treated group achieved higher levels of 25(OH)D (P < 0.001). At week 12, those patients who registered serum levels of 25(OH)D ≥20 ng/ml, regardless of whether or not they had received supplementation, showed a lower SCORAD compared to those with levels <20 ng/ml (P < 0.001). Eighty percent of the patients with serum levels <20 ng/ml (n = 9) had moderate–severe AD despite standard treatment. Vitamin D levels ≥20 ng/ml associated with baseline therapy strongly favored remission of atopic dermatitis (P = 0.03). No significant differences were found between patients with serum levels of ≥20 ng/ml vs. ≥30 ng/ml. Conclusions Reaching serum levels of 25(OH)D > 20 ng/ml in conjunction with standard therapy is sufficient to achieve a reduction in severity (SCORAD) in patients with AD.